PENGARUH PENGGUNAAN MEDIA BINGKAI 10 TERHADAP PEMAHAMAN PART-PART-WHOLE PADA ANAK USIA 6-7 TAHUN (STUDY EKSPERIMEN DI BKB PAUD ANGGREK KELURAHAN MUNJUL, KECAMATAN CIPAYUNG, JAKARTA TIMUR) - Intani Dewi Kartika Sari; Hapidin Hapidin (STIT Al-Marhalah Al-Ulya Bekasi, 2021)
AbstrackThis study aims to obtain empirical data on the effect of Ten Frame Media usedto understand Part-part-whole in 6-7 Years old at in Munjul Village, Cipayung Subdistrict, East Jakarta.The method used is kuantitatif research with experiment approach and the research design is True Experimental with Two Group Pre-test and Post-test Design (technique of pre-test and post-test with two groups randomized).The population in this study were all students aged 6-7 years which is a group of early childhood in the Munjul Village. The sample in this study is children aged 6-7 years in early childhood education for School Readiness Group (KeMaS) with a sample of 15 children in the experimental group and 15 children in the control group, which was taken by using simple random cluster technique.Data collection tools of Variable Y (Part-part-whole Understanding) is done using techniques of observation checklist. The analysis technique used is the t-test for small samples are not correlated. Based on the results ofÂ hypothesis testing using t-test is obtained price thitung1 = 22, 5 (comparative test of pre-post test Experimental Group), thitung2 = 8, 90 (Comparative test of pre-post test control group), and thitung3 = 30, 79 (Comparative test of post-post-test Experiment-Control Group), a price table = 1, 70, and dk = 28 at the significant level ? = 0.05. From these results it can be concluded that thitung ttable, so this study reject H0 (Zero Hypothetical) and receiving Ha (Alternative Hypothesis). This study therefore implies that the use of 10 frames media significant effect on the understanding part-part-whole in children aged 6-7 years. The more often a child at the age of 6-7 years using the media frame 10, then the better the understanding of the part-part-whole.Â Keywords: Ten Frame Media, Counting Principles, Part-part-whole